(untitled) (International journal of medical sciences, 2026)
In this article describes oral diseases remain among the most prevalent non-communicable diseases worldwide, significantly affecting quality of life and imposing a substantial economic burden on healthcare systems. Despite advances in dental technologies and clinical treatment, preventive strategies in oral health are still insufficiently implemented, particularly in low- and middle-income countries. Epidemiological data reveal persistent inequalities in oral health outcomes related to socioeconomic status, education level, and access to preventive care. This study is based on a narrative analytical review of recent epidemiological reports, international oral health surveys, and peer-reviewed scientific publications published between 2015 and 2024. The analysis focuses on preventive strategies, risk factor distribution, and population-level oral disease prevalence. Comparative analysis methods were used to evaluate trends in dental caries, periodontal diseases, and oral cancer across different regions.